Sosialisasi Sistem Pengendalian Internal Laporan Keuangan Yayasan Pendidikan Al – Islam Bahrul Ulum Cibubur - Rafrini Amyulianthy; Amelia Oktrivina; Indah Masri; Nelyumna Nelyumna (LPMP Imperium, 2022)
The training program on August 13, 2022, is a series of webinars with three community service activities related to the Internal Control System for the Al-Islam Bahrul Ulum Education Foundation. The results of this program include the implementation of the service has been running as expected, and Participants seem to need knowledge related to the internal control system within the Foundation; sharing knowledge and skills has been carried out and is expected to be helpful for the community, especially the Al-Islam Bahrul Education Foundation. Ulum and good communication have been established between the lecturers as academics of the Faculty of Economics and Business, Pancasila University, and the Al-Islam Bahrul Ulum Education Foundation. This communication can encourage the implementation of further cooperation that can be done by synergizing the programs of these parties.